Economic Analysis of Law on Catch Quota Based Measured Fishing Regulations in Indonesia - Masitha Tismananda Kumala; Titik Suharti; Ria Tri Vinata (Lex Portus)
The measured fishing regulation is a fisheries management regulation that maximizes the utilization of fishery resources without disrupting their sustainability which is regulated through Government Regulation Number 11 of 2023 concerning Measured Fishing (Measured Fishing Regulation) and Regulation of the Minister of Marine and Fisheries Affairs Number 28 of 2023 concerning the Implementing of Government Regulation Number 11 of 2023 (Implementing Regulation of Measured Fishing). Measured fishing in Indonesia is carried out based on a catch quota system which aims to improve the welfare of fishermen. The urgency of this study is to determine the results of the economic analysis and the economic impact of Measured Fishing Regulation and Implementing Regulation of Measured Fishing because this policy will affect the livelihoods of fishermen whose numbers are very high in Indonesia. The aim of this study is to analyze and evaluate the regulation of measured fishing in Indonesia using the Economic Analysis of Law approach and theory. There are two things studied in this study, namely First, the regulation of catch quota based measured fishing in Indonesia. Second, Economic Analysis of Law on catch quota based Measuring Fishing Regulations in Indonesia. This study uses an empirical research method by making law the object of research by considering related data. The results of the study show that fishing in Indonesia is based on a catch quota system given to each fishing vessel. The catch quota given is transferable both between fishing vessels in the same and different Fisheries Business Permit. Referring to the theory taught by Richard A. Posner, it can be said that the quota-based Measuring Fishing Regulations in Indonesia regulated through PP No. 11 of 2023 do not meet the elements of value, utility and efficiency.